Pengungkapan integrated reporting: keterlibatan stakeholder dan mekanisme corporate governance - Sugihani, Nurul; Rita Wijayanti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Integrated Reporting is a recent development reporting practice that combines financial and non-financial information into an integrated and concise manner. This study aims to examine the effect of stakeholder engagement was proxy by (ownership concentration, effective tax rate, leverage and employee compensation) and corporate governance mecanishms was proxied by (independent commissioners, frequency of audit committee meetings and gender diversity) on Integrated Reporting disclosure.The sample was selected of companies listed on the LQ-45 Index of the Indonesian Stock Exchange, through the purposive sampling method, 108 samples were obtained during the period 2017-2020. The data analysis technique used multiple linear regression with the SPSS 24 application program. Based on the results shows that the leverage, frequency of audit committee meetings and gender diversity affect on Integrated Reporting disclosure, while ownership concentration, effective tax rate, employee compensation and independent commissioners have no effect on Integrated Reporting disclosure. The implications of this research can be useful for companies to choose variables that need to be considered when preparing Integrated Reporting disclosures to stakeholders.